2020
DOI: 10.1523/jneurosci.0255-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Origin of Nociceptive-Induced Gamma-Band Oscillations

Abstract: Gamma-band oscillations (GBOs) elicited by transient nociceptive stimuli are one of the most promising biomarkers of pain across species. Still, whether these GBOs reflect stimulus encoding in the primary somatosensory cortex (S1) or nocifensive behavior in the primary motor cortex (M1) is debated. Here we recorded neural activity simultaneously from the brain surface as well as at different depths of the bilateral S1/M1 in freely-moving male rats receiving nociceptive stimulation. GBOs measured from superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 75 publications
5
29
0
1
Order By: Relevance
“…Pain-related gamma oscillatory activity in the somatosensory S1 predicts pain sensitivity (Hauck et al, 2007;Heid et al, 2020;Hu and Iannetti, 2019) and inducing gamma oscillations in SI enhances nociceptive sensitivity and induces aversive avoidance behavior (Tan et al, 2019). Furthermore, noxious laser evoked spiking in superficial S1 interneurons has strong phase coherence with gamma oscillations in awake rats (Yue et al, 2020). C fibre activity was also associated with increases in beta energy at >500ms latency post stimulus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pain-related gamma oscillatory activity in the somatosensory S1 predicts pain sensitivity (Hauck et al, 2007;Heid et al, 2020;Hu and Iannetti, 2019) and inducing gamma oscillations in SI enhances nociceptive sensitivity and induces aversive avoidance behavior (Tan et al, 2019). Furthermore, noxious laser evoked spiking in superficial S1 interneurons has strong phase coherence with gamma oscillations in awake rats (Yue et al, 2020). C fibre activity was also associated with increases in beta energy at >500ms latency post stimulus.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the amplitudes of both alpha and beta rhythms in rat S1 are suppressed by a tactile stimulus, with a comparable time course to humans (Fransen et al, 2016) and noxious skin stimulation results in selective increases in S1 gamma activity in both rodents and human subjects (Hu and Iannetti, 2019). Gamma activity reflects stimulus encoding in S1 (Yue et al, 2020) and experimental induction of S1 gamma oscillations via optogenetic activation of parvalbumin-expressing inhibitory interneurons enhances nociceptive sensitivity and induces aversive avoidance behaviour (Tan et al, 2019). Changes in other oscillatory frequencies are also reported following skin stimulation, including decreases in alpha and beta energy related to cutaneous stimulus intensity (Nickel et al, 2017) and synchronization of theta-alpha energy following noxious stimulation (Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we observed that the spectral power density of gamma band oscillations was positively correlated with the subjective report of postoperative pain. This observation provided additional evidence for the close relationship between gamma band oscillation and pain perception across different human subjects and might be related to the possible communication between distributed neuronal ensembles for subsequent pain-related behaviors [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 95%
“…此外, 在长时疼痛和慢性 [63] , 且疼痛诱发 的GBOs和听觉诱发的GBOs有明显差异 [51] . 此外, 炎 症痛小鼠的自发GBOs增强, 且其诱发GBOs与其痛觉 超敏行为相关 [64] , 提示长时疼痛下的GBOs与疼痛行 [66] , 揭示了激光热痛诱发的GBOs主要来自刺激部位对侧 S1浅层中间神经元(interneurons)放电 [67] .…”
unclassified